Teknologi Pengelolaan Sampah Organik Menggunakan Larva Black Soldier FLY Di TPS3R Kesiman Kertalangu Denpasar Bali - Wibawa, I Made Sastra; Maharani, Shinta Enggar; Nambung, Hermes Henryanto (Jurnal Ecocentrism, 2024)
Bali is a region that produces a lot of waste, reaching 4,281 tons in one day, whereas if calculated over one year, there will be as much as 52% of waste that is not managed properly. In 2022 to 2023, the total waste generation entering TPS3R Kesiman Kertalangu Denpasar is 6,039 Kg/day, consisting of organic waste of 1,569 Kg/day, and the remainder is residual waste which is disposed of in the landfill with waste generation of 4,470 Kg/day . The percentage of residual waste disposal from TPS3R Kesiman Kertalangu to TPA is 74%. This research uses experiments, which aim to: 1) find out research instrument techniques that reduce organic waste more quickly and 2) find out the BSF waste from the type of organic waste that is most in accordance with SNI Kompos 19-7030-2004. The research used two research instrument techniques, namely the Tray Instrument Technique and the Barrel Instrument Technique. The results of the research show: 1) the waste management technique using BSF larvae that reduces waste the fastest is in Instrument Tray 3 which contains 2000 grams of organic food waste which is reduced by 100 grams of BSF larvae for 16 days so that it weighs 1597 grams, and 2) BSF Kasgot that meets SNI Compost 19-7030-2004 is a waste management technique that uses Tray 3 Instruments, which has a water content of 19.040%, C-Organic 13.910%, Ph 6.970%, and N 0.980%.